Corneal Crosslinking Biomechanics Evaluated by a Novel and Easily Implemented Differential Tonometry Method. (2nd November 2021) - Wang, Mingwu; Berdahl, John; McCafferty, Sean
ABSTRACT: Purpose : Evaluate potential corneal biomechanical changes following corneal crosslinking (CXL) by paired differential tonometry intraocular pressure (IOP) measurements with a Goldmann tonometer (GAT) prism and corneal compensating, correcting applanation tonometry surface (CATS) prism. Methods : IOP was measured prospectively on 23 unique eyes undergoing CXL for keratoconus with a GAT using a standard flat GAT prism and a curved corneal error correcting CATS prism before treatment and at 2 weeks, 2 months and 6 months after treatment. Concurrent measurements of central corneal thickness (CCT) and corneal hysteresis (CH) were completed. Results : Paired IOP measurements with standard GAT and corneal correcting CATS prisms indicated a significant sustained relative increase in the differential IOP between the two prisms after CXL ( p = .002, 0.051, 0.062). CH initially decreased at two weeks post-CXL then returned to sustained pre-op levels ( p = .033, 0.20, 0.20). CCT progressively decreased following CXL ( p = .005). Discussion : Differential tonometry between standard GAT and corneal biomechanical compensating CATS prisms indicates findings consistent with increased corneal rigidity following CXL and may demonstrate a simple and sensitive method for measurement of relative corneal biomechanical changes due to pharmacologic agents and procedures.